Analysis Of Modeling Techniques Method To The Success Of Toilet Training For Toddler At Posyandu Mawar Working Area Wonorejo Health Center Kediri District - Yeny Hidajaturrokhmah, Nur; Malia Yanti Yuli Lestari; Lingga Kusuma (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2021)
Technical errors and parental attitudes in teaching toilet training. Toilet training is a task of growth and development of children toddler age for children to become independent.. The general purpose of this research is to know the Influence of Modeling Technique Method To The Success of Toilet Training For Toddler At Posyandu Mawar Working Area of Wonorejo Health Center Kediri District. The research design in this research is pre experimental design with one group pre test approach - post test design. The population of this research is all parents who have children aged 1-3 years in Posyandu Mawar. The sample size is 30 respondents taken by Simple Random Sampling technique. Variable dependent successful toilet training, variable independent method of modeling technique. The results of analysis using Mc Nemar. The result of this research was found that most of respondents who have children in the category of unsuccessful toilet training before were given 22 respondents (73.3%) modeling technique and most of the respondents who have children succeeded in doing toilet training after 27 modeling techniques (90%). The result of data analysis got p value = 0.000 <(0.05), which means that there is Influence Giving Method of Modeling Technique To Successful Toilet Training for Toddlers In Posyandu Mawar Work Area of Wonorejo Health Center Kediri Regency. Toddler-age children are often attracted to activities in the family bathroom, so it's wise to let children watch their parents when they go to the bathroom. By seeing adults using toilets, children will observe how to use the toilet so that they will have the same desire.